Decarburization mechanism of Fe-Si-Al alloy with antimony addition - Steiner Petrovič, Darja (Kovine zlitine tehnologije, 1998)
The mechanism of decarburization process of Fe-Si-Al alloy was investigated onsamples of cold rolled sheets; some of them alloyed with 0.048 wt.% Sb. The decarburization was performed in a ?$H_2H_2O$? gas mixture at 840°C. It was influenced by the oxidation of the surface. Antimony influence of on decarburization mechanism of Fe-Si-Al alloy depends on carbon content in the steel.
Keywords: jekla; razogljičenje; oksidacija; antimon; antimony; silicij; aluminij; Aluminij Mostar; aluminum